The impact of applying value added tax on the net profitability of financial services in Islamic banks in the Kingdom of Saudi Arabia - Al-Qahtani, Turki Saeed; Al-Qahtani, Abdulrahman Saad (Journal of Economic, Administrative and Legal Sciences, 2025)
The study aimed to identify the impact of applying value-added tax on the net profitability of financial services in Islamic banks in the Kingdom of Saudi Arabia, which number 4 banks, during the years 2017, 2018, and 2021. Profitability was measured through indicators (return on assets, return on share, return on equity). The study relied on the descriptive analytical approach in collecting, analyzing and describing data related to the study variables from the financial statements of Islamic banks during the study years. Linear regression was used as a statistical method. The study concluded that there was no statistically significant positive impact at the level (α ≥ 0.05) of applying value-added tax on the net profitability of financial services (represented by return on assets, return on share, return on equity) in Islamic banks in the Kingdom of Saudi Arabia. In light of these results, the study recommended the necessity of continuing the policy of exempting value-added tax on the main financial services provided by Saudi Islamic banks, as previous results show that this exemption has contributed positively to developing the banking sector and increasing its competitiveness. It is also necessary for Saudi banks to work on developing and marketing financial services exempt from value-added tax, such as loans and direct cash facilities, to increase demand for them and enhance the role of banks as an intermediary for collecting taxes.
Keywords: Value Added Tax; Net profitability; Islamic Banks